2018
DOI: 10.1093/neuonc/noy177
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and vascular permeability correlate with growth in sporadic vestibular schwannoma

Abstract: BackgroundInflammation is hypothesized to be a key event in the growth of sporadic vestibular schwannoma (VS). In this study we sought to investigate the relationship between inflammation and tumor growth in vivo using the PET tracer 11C-(R)-PK11195 and dynamic contrast enhanced (DCE) MRI derived vascular biomarkers.MethodsNineteen patients with sporadic VS (8 static, 7 growing, and 4 shrinking tumors) underwent prospective imaging with dynamic 11C-(R)-PK11195 PET and a comprehensive MR protocol, including hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
103
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(115 citation statements)
references
References 49 publications
11
103
1
Order By: Relevance
“…Considering the bias of ASCAT only calling heterogeneity in tumors with large aberration and the variant allele frequencies reported in our WES study, it seems likely that most or all VSs consists of more than one major genetic clone. A recent study by Lewis et al found that tumor-associated macrophages constituted 50-60% of the cells in eight growing VSs [33]. Hence, infiltrating macrophages might constitute the clone coexisting with the neoplastic cells.…”
Section: Discussionmentioning
confidence: 95%
“…Considering the bias of ASCAT only calling heterogeneity in tumors with large aberration and the variant allele frequencies reported in our WES study, it seems likely that most or all VSs consists of more than one major genetic clone. A recent study by Lewis et al found that tumor-associated macrophages constituted 50-60% of the cells in eight growing VSs [33]. Hence, infiltrating macrophages might constitute the clone coexisting with the neoplastic cells.…”
Section: Discussionmentioning
confidence: 95%
“…Concerning pathophysiology, it can be assumed that local residual cells with higher mitotic activity driven by inflammation will disturb the local function of the facial nerve by contributing to the formation of scars. Lewis et al [27] suggested that inflammation is a relevant parameter when evaluating the growth of vestibular schwannomas. Positive correlations between higher MIB-1 index values and the presence of CD68positive macrophages and CD45-positive lymphocytes were also observed in our study.…”
Section: Mib-1 Proliferation Indexmentioning
confidence: 99%
“…Positive correlations between higher MIB-1 index values and the presence of CD68positive macrophages and CD45-positive lymphocytes were also observed in our study. In an investigation by Lewis et al [27], tumour tissues obtained from 8 sporadic VSs were immunohistochemically analysed, and the growing tumours were found to exhibit significantly higher proportions of Ki-67/Iba1 (ionised calcium-binding adapter molecule)-positive cells. Additionally, programmed cell death 1 ligand 1 (PD-L1) expression was recently described in VSs [5], and it was suggested that PD-L1 expression, tumour-associated macrophages, and rapid tumour growth could be correlated with each other.…”
Section: Mib-1 Proliferation Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…These clinical observations suggest additional explanations for the pathophysiology of SNHL, beyond only mechanical compression of adjacent structures. Recent studies have revealed new insights about the capacity of secreted factors, such as tumor necrosis factor alpha (TNFα), and extracellular vesicles (EVs) from human VSs to cause cochlear damage (11)(12)(13)(14)(15)(16). The greater the severity of SNHL associated with a VS tumor, the greater the degree of hair cell loss and neuronal fiber disorganization seen in cochlear explants exposed to tumor secretions (11,13).…”
Section: Introductionmentioning
confidence: 99%